2009
DOI: 10.1128/aem.02216-08
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diversity of the Bifidobacterial Population in the Human Intestinal Tract

Abstract: Although the health-promoting roles of bifidobacteria are widely accepted, the diversity of bifidobacteria among the human intestinal microbiota is still poorly understood. We performed a census of bifidobacterial populations from human intestinal mucosal and fecal samples by plating them on selective medium, coupled with molecular analysis of selected rRNA gene sequences (16S rRNA gene and internally transcribed spacer [ITS] 16S-23S spacer sequences) of isolated colonies. A total of 900 isolates were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
215
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 282 publications
(253 citation statements)
references
References 60 publications
13
215
2
6
Order By: Relevance
“…Several ecological studies have shown that bifidobacteria are a dominant bacterial group of the infant microbiota as well as a key component of the adult-type intestinal microbiota (8,43). It is believed that bifidobacteria are well adapted to maximize metabolic access to a wide variety of diet-derived and/or hostderived sugars (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ecological studies have shown that bifidobacteria are a dominant bacterial group of the infant microbiota as well as a key component of the adult-type intestinal microbiota (8,43). It is believed that bifidobacteria are well adapted to maximize metabolic access to a wide variety of diet-derived and/or hostderived sugars (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Breast-fed infants develop an enteric microbiota that typically contains high levels of bifidobacteria (1, 7) in which species like Bifidobacterium bifidum are abundant (8). The ability of B. bifidum to grow on mucin has been noted previously (9), and this organism also possesses a metabolic pathway for the degradation of lacto-N-biose and galacto-N-biose (10,11), which constitute the building blocks of human milk oligosaccharides (HMO) and the core 1 structure of mucin-type O-glycan, respectively (12).…”
mentioning
confidence: 99%
“…These differences occur probably because the latter techniques highlight only those bifidobacteria that can be cultivated on synthetic media or that can be discriminated on the basis of the different melting temperatures of small fragments of their rRNA genes (Turroni et al, 2008(Turroni et al, , 2009). However, the nutritional requirements of bifidobacteria are still largely unknown, and largely depend on the ecophysiological state of each strain, which is extremely variable in a complex ecosystem like that of the human gut (Ventura et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Within the human gut some microbial members are permanently established (mucosaadherent components), whereas others may represent transient members (Ley and Peterson DA Gordon, 2006;Turroni et al, 2008Turroni et al, , 2009. It is noted that the mucosa-adherent community seems to be different from the luminal community, which in turn resembles the fecal microbiota (Eckburg et al, 2005;Turroni et al, 2009). However, several studies employing 16S rRNA-based fluorescent probes have suggested that commensal bacteria may live in suspension in the lumen without being in direct contact with the gut epithelium ( Van der Waaij et al, 2005;Swidsinski et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation